The Chronology of Microfinance Development in Malaysia: A Review - Ahmad Nazrie, Mohd Nor; T., Senthil Kumar (KnE Social Sciences, 2019)
This study is to discover the development of microfinance in Malaysia through a review of relevant literature. Microfinance in Malaysia, especially the operations of Amanah Ikthiar Malaysia, are based on Grameen Bank Program innovated by Muhammad Yunus in Bangladesh. Malaysia is endeavoring to be a developed nation, and new age microfinance seems to play a crucial role in eradicating poverty. Poverty and development do not complement each other, and hence, it is essential to focus on poverty eradication through various means. Here, an attempt has been made to the methodological and systematical review of the past literature on the development of microfinance, from various sources. It is hoped that this paper would provide a better understanding of the chronological flow and evolution of microfinance in Malaysia.